Folate Receptor β Targeted PET Imaging of Macrophages in Autoimmune Myocarditis - Arghavan Jahandideh; Sauli Uotila; Mia Ståhle; Jenni Virta; Xiang-Guo Li; Ville Kytö; Päivi Marjamäki; Heidi Liljenbäck; Pekka Taimen; Vesa Oikonen; Jukka Lehtonen; Mikko I. Mäyranpää; et al. (SOC NUCLEAR MEDICINE INC, 2022)
Rationale: Currently available imaging techniques have limited specificity for the detection of active myocardial inflammation. Aluminum fluoride-18-labeled 1,4,7-triazacyclononane-N,N′,N″-triacetic acid conjugated folate (18F-FOL) is a positron emission tomography (PET) tracer targeting folate receptor β (FR-β) that is expressed on activated macrophages at sites of inflammation. We evaluated 18F-FOL PET for the detection of myocardial inflammation in rats with autoimmune myocarditis and studied expression of FR-β in human cardiac sarcoidosis specimens.
Methods: Myocarditis was induced by immunizing rats (n = 18) with porcine cardiac myosin in complete Freund’s adjuvant. Control rats (n = 6) were injected with Freund’s adjuvant alone. 18F-FOL was intravenously injected followed by imaging with a small animal PET/computed tomography (CT) scanner and autoradiography. Contrast-enhanced high-resolution CT or 2-deoxy-2-18F-fluoro-D-glucose (18F-FDG) PET images were used for co-registration. Rat tissue sections and myocardial autopsy samples of 6 patients with cardiac sarcoidosis were studied for macrophages and FR-β.
Results: The myocardium of 10 out of 18 immunized rats showed focal macrophage-rich inflammatory lesions with FR-β expression occurring mainly in M1-polarized macrophages. PET images showed focal myocardial 18F-FOL uptake co-localizing with inflammatory lesions (SUVmean, 2.1 ± 1.1), whereas uptake in the remote myocardium of immunized rats and controls was low (SUVmean, 0.4 ± 0.2 and 0.4 ± 0.1, respectively; P < 0.01). Ex vivo autoradiography of tissue sections confirmed uptake of 18F-FOL in myocardial inflammatory lesions. Uptake of 18F-FOL to inflamed myocardium was efficiently blocked by a non-labeled FR-β ligand folate glucosamine in vivo. The myocardium of patients with cardiac sarcoidosis showed many FR-β-positive macrophages in inflammatory lesions. Conclusion: In a rat model of autoimmune myocarditis, 18F-FOL shows specific uptake in inflamed myocardium containing macrophages expressing FR-β, which were also present in human cardiac sarcoid lesions. Imaging of FR-β expression is a potential approach for the detection of active myocardial inflammation.